Writing reaction mechanisms in organic chemistry - Miller, Audrey (Advanced organic chemistry series., 2000)
Writing Reaction Mechanisms in Organic Chemistry, Second Edition, is an invaluable guide to charting the movements of atoms and electrons in the reactions of organic molecules. Miller and Solomon illustrate that understanding organic reactions is based on applying general principles rather than the rote memorization of unrelated processes, and, in turn, emphasize that writing mechanisms is a practical method of applying knowledge of previously encountered reactions and reaction conditions to new reactions. Students and research chemists alike will find this book useful in providing a method of organizing and synthesizing an oftentimes overwhelming quantity of information into a set of general principles and guidelines for determining and describing organic reaction mechanisms. * Essential for those students who need to have mechanisms explained in greater detail than most organic chemistry textbooks provide. * Illustrated with hundreds of chemical structures * Extensively rewritten and reorganized to make the presentation and format even easier for students to use * Contains many problem sets and answers to all problems to help students work through general principles and applications * Appendixes have been added to this edition that contain easily referenced information on Lewis structures, symbols for chemical notation, and the relative acidities of common substances.